Markers of gut dysfunction do not explain low rifampicin bioavailability in HIV-associated TB. (2nd May 2017) - Vinnard, Christopher; Ravimohan, Shruthi; Tamuhla, Neo; Pasipanodya, Jotam; Srivastava, Shashikant; Modongo, Chawangwa; Zetola, Nicola M.; Weissman, Drew; Gumbo, Tawanda; Bisson, Gregory P.
Abstract: Background: Rifampicin is the key drug responsible for sterilizing activities in the first-line TB treatment regimen. Damage to the gut during acute and chronic HIV infection may inhibit drug absorptive capacity. We sought to test the hypothesis that markers of intestinal damage, bacterial translocation and systemic immune activation would relate to rifampicin bioavailability among HIV/TB patients. Patients and methods: We conducted a prospective cohort study of rifampicin pharmacokinetics in HIV/TB patients in Gaborone, Botswana. We performed two intensively sampled pharmacokinetic visits, before and after ART initiation. Non-linear mixed-effects modelling was performed to determine whether variability in markers of gut damage, microbial translocation or systemic immune activation contributed to variability in rifampicin bioavailability before and after the initiation of ART. Results: We enrolled 40 HIV/TB patients in the first pharmacokinetic visit and 24 patients returned for the second pharmacokinetic visit after initiating ART. Low rifampicin exposure, as defined by the maximum serum concentration, was observed in 40% of patients prior to initiating ART and 46% of patients after initiating ART. In the non-linear mixed-effects model, we did not observe significant covariate effects of markers of gut damage, microbial translocation or immune activation on rifampicin bioavailability before and after ART initiation. Discussion: Markers of intestinal damage, microbial translocation and systemic immune activation did not explain variability in rifampicin bioavailability. The a priori identification of HIV/TB patients at risk for low rifampicin concentrations remains a challenge, supporting a role for therapeutic drug monitoring during HIV/TB therapy.